Development of distance glove for blind people as an alternative tool - Nugroho Prasetya Adi; Rahayu Agustin (Universitas Sultan Ageng Tirtayasa, 2020)
The eye was one of the senses that functions to record a state or condition so that humans could know the object they see. However, not all humans were created with normal eye conditions; some had visual disturbances from birth. Blind people generally use a walking aid in the form of a cane or a trained dog to help with movement and increase safety and independence during activities. This research aimed to produce gloves as a tool for blind people who had a distance accuracy from the ultrasonic sensor. This research was a research development (R&D). The results showed that the average error percentage was 1.75% for the ultrasonic sensor one and the average error percentage was 2.13% for the ultrasonic sensor 2. So it can be concluded that the research data obtained has a research accuracy of 98.25% for the ultrasonic sensor 1 and 97.87% for the sensor. Ultrasonic 2. The maximum distance that the two ultrasonic sensors can read is 55 cm; at that distance, the two ultrasonic sensors will work properly. For distances above the maximum distance, the ultrasonic sensor cannot do.